2015
DOI: 10.1210/me.2014-1293
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Melatonin Signaling Promotes β-Cell Survival and Function

Abstract: Type 2 diabetes mellitus (T2DM) is characterized by pancreatic islet failure due to loss of β-cell secretory function and mass. Studies have identified a link between a variance in the gene encoding melatonin (MT) receptor 2, T2DM, and impaired insulin secretion. This genetic linkage raises the question whether MT signaling plays a role in regulation of β-cell function and survival in T2DM. To address this postulate, we used INS 832/13 cells to test whether activation of MT signaling attenuates proteotoxicity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 55 publications
4
59
0
5
Order By: Relevance
“…Our data suggested that decreased melatonin signalling through deleterious MT2 receptor activity increases type 2 diabetes risk. These conclusions were in line with various studies done in rodents, beta cells and human cohorts, which showed that high melatonin levels, or the administration of melatonin or of melatonergic agonists, lead to decreased (and not augmented) risk of diabetes [9,13,14]. Indeed, for instance, a 12 year prospective study including 370 women who developed type 2 diabetes and 370 matched control participants showed that decreased levels of melatonin secretion during the night is independently associated with a higher risk of developing type 2 diabetes [13].…”
Section: Decreased Melatonin Signalling and Type 2 Diabetes Risksupporting
confidence: 90%
See 1 more Smart Citation
“…Our data suggested that decreased melatonin signalling through deleterious MT2 receptor activity increases type 2 diabetes risk. These conclusions were in line with various studies done in rodents, beta cells and human cohorts, which showed that high melatonin levels, or the administration of melatonin or of melatonergic agonists, lead to decreased (and not augmented) risk of diabetes [9,13,14]. Indeed, for instance, a 12 year prospective study including 370 women who developed type 2 diabetes and 370 matched control participants showed that decreased levels of melatonin secretion during the night is independently associated with a higher risk of developing type 2 diabetes [13].…”
Section: Decreased Melatonin Signalling and Type 2 Diabetes Risksupporting
confidence: 90%
“…Therefore, in studies that aim to analyse the effect of melatonin physiologically, it is crucial to be aware that results found in nocturnal rodents can be opposite to those in diurnal humans. For instance, there are conflicting in vitro studies on the impact of melatonin on insulin secretion from rodent and human islets; in rodent beta cells melatonin was shown to decrease insulin secretion [1,8], whilst in one study of human islets, melatonin was observed to potentiate insulin secretion [9].…”
Section: The Variable Effect Of Melatoninmentioning
confidence: 99%
“…In this context, a role for melatonin in the insulin secretory response of ␤-cells to GLP-1 stimulation has been suggested. Thus, it has been shown that short-term exposure to melatonin attenuates the stimulatory effects elicited by GLP-1 in vitro, whereas more prolonged exposure times (12 h), resembling the natural overnight exposure to high melatonin levels, have been associated with enhanced sensitivity to GLP-1 stimulation (11,22). These findings support the hypothesis that ␤-cells may be more sensitive to GLP-1 effects in the morning than at the beginning of the dark period.…”
Section: Discussionmentioning
confidence: 54%
“…Together, these data suggest that melatonin can have both stimulatory and inhibitory influences on insulin secretion. Notably, in vitro melatonin administration protects beta cells from the deleterious effects of glucose toxicity, improving beta cell survival, and reducing oxidative stress responses in both INS-1 832/13 rodent beta cells and isolated human islets from individuals with type 2 diabetes [115,116]. In vivo, chronic treatment with melatonin (10 mg kg −1 day −1 ) was also able to partially restore beta cell mass in a rat model of streptozotocin (STZ)-induced diabetes [117].…”
Section: The Pancreatic Response To Melatoninmentioning
confidence: 99%
“…Evidence from animal and human studies indicates that melatonin or synthetic melatonin receptor agonists can alter glucose homeostasis [5,145,153]. The study of isolated human islets from both healthy and type 2 diabetic donors has revealed that melatonin can normalise glucose-stimulated insulin secretion following exposure to hyperglycaemia [115]. Moreover, recent randomised controlled trials suggest that chronic treatment with melatonin in combination with oral blood glucose lowering agents improves fasting and postprandial glycaemic control and reduces HbA 1c levels [152,154].…”
Section: Clinical Evidencementioning
confidence: 99%